Introduction to Cybersecurity for Teachers and Students in Indonesia in the Digital Era (Pengenalan Keamanan Siber bagi Guru dan Siswa di Indonesia di Era Digital) - Octiva, Cut Susan; Rahayu, Novi; Laia, Mitranikasih; Suryadi, Dikky; Hakim, Muhammad Lukman (Indonesia Berdaya, 2025)
This Community Service (PKM) activity aims to increase cybersecurity literacy among teachers and students as part of efforts to support digital transformation in education. The training was conducted online with an interactive approach, involving 50 participants from various schools in Indonesia. The material includes an introduction to cyber threats, mitigation strategies, and daily digital security practices. The evaluation was done through pre-test and post-test, accompanied by a participant satisfaction questionnaire. The results showed a significant improvement in participants' understanding, with an average score increase of 73%. The level of satisfaction of participants with the training reached the "excellent" category with an average score of 4.75 on a scale of 5. These findings reflect the effectiveness of the designed training methods. However, the limitations of digital infrastructure are the main challenge in implementing activities. This Activity has contributed positively to building cybersecurity awareness and literacy in the education sector. In addition to providing direct benefits to participants, this program is expected to be a model for similar training that supports the sustainable strengthening of digital literacy in Indonesia.Abstrak. Kegiatan Pengabdian Kepada Masyarakat (PKM) ini bertujuan untuk meningkatkan literasi keamanan siber di kalangan guru dan siswa sebagai bagian dari upaya mendukung transformasi digital dalam pendidikan. Pelatihan dilakukan secara daring dengan pendekatan interaktif, melibatkan 50 peserta dari berbagai sekolah di Indonesia. Materi yang diberikan meliputi pengenalan ancaman siber, strategi mitigasi, dan praktik keamanan digital sehari-hari. Evaluasi dilakukan melalui pre-test dan post-test, disertai dengan kuesioner kepuasan peserta. Hasil penelitian menunjukkan adanya peningkatan pemahaman peserta yang signifikan, dengan peningkatan skor rata-rata sebesar 73%. Tingkat kepuasan peserta terhadap pelatihan mencapai kategori “sangat baik” dengan skor rata-rata 4,75 dari skala 5. Temuan ini mencerminkan efektivitas metode pelatihan yang dirancang. Namun, keterbatasan infrastruktur digital menjadi tantangan utama dalam pelaksanaan kegiatan. Kegiatan ini telah memberikan kontribusi positif dalam membangun kesadaran dan literasi keamanan siber di sektor pendidikan. Selain memberikan manfaat langsung kepada peserta, program ini diharapkan dapat menjadi model pelatihan serupa yang mendukung penguatan literasi digital di Indonesia secara berkelanjutan.